'And All is Real.' Historical Spaces and Special F/X in HBO's Rome. Issue 3 (November 2013) - Elliott, Andrew B.R.
This essay explores the use of special effects in HBO's Rome . Looking at depictions of the classical past, it argues that special effects were traditionally used in the cinema to heighten verisimilitude by a sense of spectacle, whose cost put them out of reach of early historical television. With the increase in budgets and the greater affordability of special effects, however, this paper suggests that Rome signals a new kind of classical world on television, wherein special effects not only enhance verisimilitude by a kind of spectacle but also serve a narrative function.